Oral Vaccination Based on DNA-Chitosan Nanoparticles against Schistosoma mansoni Infection - Carolina R. Oliveira; Cíntia M. F. Rezende; Marina R. Silva; Olga M. Borges; Ana P. Pêgo; Alfredo M. Goes (The Scientific World Journal)
The development of a vaccine would be essential for the control of schistosomiasis, which is recognized as the most important human helminth infection in terms of morbidity and mortality. A new approach of oral vaccination with DNA-chitosan nanoparticles appears interesting because of their great stability and the ease of target accessibility, besides chitosan immunostimulatory properties. Here we described that chitosan nanoparticles loaded with plasmid DNA encoding Rho1-GTPase protein of Schistosoma mansoni, prepared at different molar ratios of primary amines to DNA phosphate anion (N/P), were able to complex electrostatically with DNA and condense it into positively charged nanostructures. Nanoparticles were able to maintain zeta potential and size characteristics in media that simulate gastric (SGF) and intestinal fluids (SIF). Further in vivo studies showed that oral immunization was not able to induce high levels of specific antibodies but induced high levels of the modulatory cytokine IL-10. This resulted in a significative reduce of liver pathology, although it could not protect mice of infection challenge with S. mansoni worms. Mice immunized only with chitosan nanoparticles presented 47% of protection against parasite infection, suggesting an important role of chitosan in inducing a protective immune response against schistosomiasis, which will be more explored in further studies.